Influence of complexing agent on the growth of chemically deposited Ni3Pb2S2 thin films - Ho, Soon Min (Oriental Scientific Publishing, 2014)
Ni 3 Pb 2 S 2 thin films were prepared by chemical bath deposition method. Here, the objective of this research is to investigate the influence of complexing agent on the properties of films.These films were characterized using atomic force microscopy, UV-Visible spectrophotometery and X-ray diffraction. It was found that the increase in the concentration of tartaric acid, film thickness increased, but, the band gap reduced. For the films prepared using 0.1M of tartaric acid, were found uniform and completely covered with the substrates.